Remote ischaemic preconditioning shortens QT intervals during exercise in healthy subjects. Issue 8 (16th November 2016) - Caru, Maxime; Lalonde, François; Gravel, Hugo; Daigle, Chantal; Tournoux, François; Jacquemet, Vincent; Curnier, Daniel
Abstract: The protective action of remote ischaemic preconditioning (RIPC) has been demonstrated in the context of surgical interventions in cardiology. Application of RIPC to sports performance has been proposed, but its effect on the electrocardiogram (ECG) during exercise remains unknown. This exploratory study aims to measure the changes in ventricular repolarization observed during exercise following RIPC in healthy subjects. In an experimental randomized crossover study, 17 subjects underwent two bouts of constant load exercise tests at 75% and 115% of gas exchange threshold (GET). Prior to exercise, they were allocated to either control or RIPC intervention with four cycles of 5 min of ischaemia followed by 5 min of reperfusion. ECG was continuously recorded during the protocol. QT and RR intervals were measured every 30 s (on an average tracing of the preceding 10 s). Although the time course of RR intervals did not differ between the two interventions ( p  = .56 at 75% GET and p  = .74 at 115% GET), a significant shortening of QT intervals (measured from Q onset to T end) was observed during exercise (mean ± standard deviation of RIPC vs. control: −32 ± 19 ms at 75% GET ( p  < .001) and −34 ± 12 ms at 115% GET ( p  < .001)) as well as during recovery (−21 ± 8 ms at 75% GET ( p  < .001) and −16 ± 11 ms at 115% GET ( p  < .001)). This effect was not present at rest. These RIPC-related changes were clearly identifiable on the QT–RR loops after hysteresis reduction. RIPC therefore induces heart rate-independent shortening of QT intervals that is revealed during exercise.